2022
DOI: 10.1186/s12884-022-05267-w
|View full text |Cite
|
Sign up to set email alerts
|

16p13.11 microdeletion/microduplication in fetuses: investigation of associated ultrasound phenotypes, genetic anomalies, and pregnancy outcome follow-up

Abstract: Objectives 16p13.11 microdeletion/microduplication are rare genetic diseases with incomplete penetrance, most of which have been reported in adults and children, with ultrasound phenotyping in fetuses rarely described. Here, we have analyzed prenatal ultrasound phenotypic characteristics associated with 16p13.11 microdeletion/microduplication, in order to improve the understanding, diagnosis and monitoring of this disease in the fetus. Methods A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…CNVs have been detected in pregnant women with fetal USMs, suggesting that more attention should be paid to CNVs in pregnant women with fetal USMs, especially P CNVs [8, 13,[23][24][25][26]. In our study cohort, CNVs were more common than aneuploidies.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…CNVs have been detected in pregnant women with fetal USMs, suggesting that more attention should be paid to CNVs in pregnant women with fetal USMs, especially P CNVs [8, 13,[23][24][25][26]. In our study cohort, CNVs were more common than aneuploidies.…”
Section: Discussionmentioning
confidence: 79%
“…Copy number analysis is a well-known rst-tier approach for the prenatal diagnosis of fetuses with structural anomalies [11] and has also recently been used for the genetic etiological diagnoses of fetuses with USM. Previous studies have suggested an association between pathogenic (P) copy-number variants (CNVs) and second-trimester USM, such as EIF and echogenic bowel associated with 16p13.11 recurrent microdeletion, mild ventriculomegaly and CPCs associated with 1q21.1 recurrent microduplication, echogenic bowel associated with the 17q12 recurrent region, and ARSA associated with 22q11.2 deletions [8, 12,13]. Chromosomal microarray (CMA) and next-generation sequencing-based CNV analysis (CNV-seq) are used to detect CNVs in fetuses with USMs via invasive prenatal diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical phenotype of 16p13.11 recurrent microduplication varies greatly, which can be manifested as autism spectrum disorder, learning difculties, brain MRI abnormalities, heart malformation and other abnormalities. The penetrance was approximately 7–8%, and about 80% of the cases are inherited from the father or mother with normal phenotype [ 33 35 ]. Therefore, this poses challenges for prenatal counseling because the associated neurodevelopmental phenotypes cannot be ascertained prenatally and it is difficult to quantify the risk to the fetus.…”
Section: Discussionmentioning
confidence: 99%